2016
DOI: 10.18632/oncotarget.7665
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of plant extracts that greatly delay yeast chronological aging and have different effects on longevity-defining cellular processes

Abstract: We discovered six plant extracts that increase yeast chronological lifespan to a significantly greater extent than any of the presently known longevity-extending chemical compounds. One of these extracts is the most potent longevity-extending pharmacological intervention yet described. We show that each of the six plant extracts is a geroprotector which delays the onset and decreases the rate of yeast chronological aging by eliciting a hormetic stress response. We also show that each of these extracts has diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(58 citation statements)
references
References 117 publications
2
56
0
Order By: Relevance
“…This network of signaling pathways and protein kinases coordinates certain longevity-defining cellular processes, including stress responses, protein synthesis in the cytosol and mitochondria, maintenance of nuclear and mitochondrial genomes, autophagy, mitochondrial respiration, peroxisome biogenesis, gluconeogenesis, lipid metabolism, glyoxylate cycle, glycogen synthesis and degradation, and the synthesis of amino acids and fatty acids [1, 6, 11, 2732, 59, 6173] (Figure 1). Information flow along this network in yeast is controlled by such aging-delaying chemical compounds as resveratrol, rapamycin, caffeine, spermidine, myriocin, methionine sulfoxide, lithocholic acid and cryptotanshinone [3, 5, 6, 810, 12, 14, 43, 54, 7478]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This network of signaling pathways and protein kinases coordinates certain longevity-defining cellular processes, including stress responses, protein synthesis in the cytosol and mitochondria, maintenance of nuclear and mitochondrial genomes, autophagy, mitochondrial respiration, peroxisome biogenesis, gluconeogenesis, lipid metabolism, glyoxylate cycle, glycogen synthesis and degradation, and the synthesis of amino acids and fatty acids [1, 6, 11, 2732, 59, 6173] (Figure 1). Information flow along this network in yeast is controlled by such aging-delaying chemical compounds as resveratrol, rapamycin, caffeine, spermidine, myriocin, methionine sulfoxide, lithocholic acid and cryptotanshinone [3, 5, 6, 810, 12, 14, 43, 54, 7478]. …”
Section: Introductionmentioning
confidence: 99%
“…We have recently discovered six plant extracts (PEs) that increase yeast chronological lifespan (CLS) to a greater extent than any of the presently known longevity-extending chemical compounds [78]. We demonstrated that each of these PEs (which we call PE4, PE5, PE6, PE8, PE12 and PE21) decelerates chronological aging and has different effects on certain longevity-defining cellular processes [78].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This response consists in the ability of yeast to develop mechanisms of protection against cellular damage caused by the mildly toxic molecules of bile acids (Goldberg et al, 2010a,b; Burstein et al, 2012a). Of note, our analysis of how different concentrations of LCA impact yeast longevity has revealed that this bile acid delays yeast chronological aging by eliciting a hormetic stress response (Goldberg et al, 2010b; Burstein et al, 2012a), which is characterized by a non-linear and biphasic dose–response curve (Goldberg et al, 2010a; Calabrese and Mattson, 2011; Burstein et al, 2012a; Calabrese et al, 2012; Leonov et al, 2015; Lutchman et al, 2016). Our recent studies also demonstrated that the ability of LCA to elicit such longevity-extending stress response is due in part to alterations in mitochondrial functionality caused by LCA, including changes in the age-related chronology of mitochondrial respiration (Goldberg et al, 2010b; Burstein et al, 2012b; Beach et al, 2013, 2015a,b; Arlia-Ciommo et al, 2014a,b; Burstein and Titorenko, 2014; Medkour and Titorenko, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Akin to cell susceptibili-ty to apoptotic and liponecrotic forms of cell death, such resistance to acute stresses is one of the key traits of early-life fitness [12, 48, 58, 61, 65, 99, 100, 104 - 109]. …”
Section: Resultsmentioning
confidence: 99%